2007
DOI: 10.1007/s11104-007-9326-1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of plant species mediated plant competition for inorganic nitrogen with soil microorganisms in an alpine meadow

Abstract: Sources of competition for limited soil resources, such as nitrogen, include competitive interactions among different plant species and between plants and soil microbes. We hypothesized that plant interactions intensified plant competition for inorganic nitrogen with soil microorganisms. To test these competitive interactions, one dominant species (Kobresia humilis Serg) and one less abundant gramineous herb (Elymus nutans Griseb) in an alpine ecosystem were selected as target species to grow under interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 48 publications
(45 reference statements)
1
36
0
Order By: Relevance
“…The leaf N : P ratios of grasses in this study were low (12.8) and comparable to those of subarctic grasses (13.2), but considerably lower than the global average for grasses (17.8) (Güsewell, 2004). This indicates that grasses growing at high altitudes or in cold climates may be more N-limited than those growing in warmer climates due to the slow mineralization of soil organic matter caused by low temperature (Zhou, 2001;Song et al, 2007) as well as lower N 2 fixation by legumes. Positive responses in the above-ground biomass for grasses to NH 4 and NO À 3 application (Table 3) confirm that they are limited or co-limited by available N and P in alpine meadows.…”
Section: Nutrient Limitation At the Plant Functional Group Levelmentioning
confidence: 50%
See 1 more Smart Citation
“…The leaf N : P ratios of grasses in this study were low (12.8) and comparable to those of subarctic grasses (13.2), but considerably lower than the global average for grasses (17.8) (Güsewell, 2004). This indicates that grasses growing at high altitudes or in cold climates may be more N-limited than those growing in warmer climates due to the slow mineralization of soil organic matter caused by low temperature (Zhou, 2001;Song et al, 2007) as well as lower N 2 fixation by legumes. Positive responses in the above-ground biomass for grasses to NH 4 and NO À 3 application (Table 3) confirm that they are limited or co-limited by available N and P in alpine meadows.…”
Section: Nutrient Limitation At the Plant Functional Group Levelmentioning
confidence: 50%
“…Although a large amount of nitrogen (N) is stored in alpine meadow soils, plant growth has frequently been reported to be co-limited by the availability of N and phosphorus (P) (Zhou, 2001). A previous study on alpine meadows showed that N mineralization is dominated by microbial immobilization during the growth season (Song et al, 2007). Additionally, these meadows in the eastern Tibetan Plateau experience N deposition of 7-10 kg N ha -1 y -1 through rainfall (Zuo et al, 1986;Lü and Tian, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the N-limited alpine meadow, the ability of plants to capture soil inorganic N was much stronger than that of soil microorganisms. Moreover, plants prefer to use soil NO 3 − -N rather than soil NH 4 + -N during the entire growing season (Song et al 2007). This may be the main reason for the lack of NO 3 − -N accumulation in the soil N pool after 3-years of chronic N additions.…”
Section: N Addition Changes Soil Variables and Plant Growthmentioning
confidence: 99%
“…Consequently, plant growth in these grasslands is often limited by available N supplies (Haselwandter et al 1983;Song et al 2007) because a seasonal demand for N by grasses often exceeds estimated seasonal release by mineralization (Körner 2003;Cao et al 2004).…”
Section: Introductionmentioning
confidence: 99%